In Silico Study of Phytochemical Compounds from Mekai (Albertisia papuana Becc.) Leaves as Anti-Breast Cancer Agents - Miningsih Miningsih; Dora Dayu Rahma Turista; Masitah Masitah; Rusni Ernopita Ulan; Risty Geofani; Dorce Bani; Sintya Sintya; Vera Damayanti (Jurnal Mandala Pharmacon Indonesia, 2026)
Breast cancer is a disease that is most commonly suffered by women, with the highest number of cases and mortality rates in the world. Current breast cancer treatment still has limitations and causes serious side effects, thus encouraging the exploration of alternative therapies based on natural sources or phytochemicals. The purpose of this study is to investigate the potential anti-breast cancer properties of the traditional herbal plant Mekai (Albertisia papuana Becc.) using an in silico approach. Molecular docking analysis of JNK and EGFR targets showed that several compounds had relatively high binding affinities (-10.1 to -9.3 kcal/mol) comparable to the positive control doxorubicin, while NUDT5 had relatively moderate binding affinities to each compound. Among these compounds, 7H-dibenzo-c,g-carbazole showed the strongest binding affinity to JNK (-10.1 kcal/mol), making it potentially the most promising candidate compound. Evaluation based on Lipinski's rules shows that selected compounds from Mekai (Albertisia papuana Becc.) leaves meet the basic parameters for drug candidates and ADME-Tox predictions, including moderate toxicity (class IV), thus supporting their suitability for further development as anticancer agent candidates, while also providing a scientific basis for the use of traditional Dayak medicinal plants in the development of natural breast cancer therapies. Further research is recommended in vitro and in vivo to confirm its efficacy, safety, and clinical relevance.